Theory of computer science : automata, languages and computation - Mishra, K.L.P (Prentice Hall of India, 2004)
Theory of computer science : automata, languages and computation / Mishra, K.L.P.. -- New Delhi: Prentice Hall of India, 2004 006.3 M678e2 2nd ed. No. of Copies : 1